ANALISIS NILAI ASET TETAP PADA LAPORAN KEKAYAAN MILIK DESA - Eko Febri Lusiono (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2019)
The initial findings of this research problem began with the 2016 and 2017 Semata Village Ownership Wealth Reports which were reported to be not in accordance with the Realization of the Semata Village Revenue and Expenditure (APB) for the year concerned, namely in Fixed Asset Valuation. Permendagri number 113 of 2014 concerning Village Financial Management and Permendagri number 1 of 2016 concerning Village Asset Management as the basis of applied theory to solve research problems. This applied research was conducted with triangulation data collection techniques and data analysis methods from Miles and Hubermann. The results of the study revealed that the 2016 and 2017 Semata Village Ownership Wealth Reports were not in accordance with regulations related to Village Financial Management and Village Asset Management in force in Indonesia. Based on interviews, the parties related to village financial management, namely the Village Head, Village Secretary, and Village Treasurer are still imperfect in understanding the technicalities of Village Property Wealth Reports, these factors being one of the causes of the Village Property Report. Applied recommendations for solving problems have been presented in the analysis of this research data.